2021
DOI: 10.3390/metabo11090601
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Inositol Pyrophosphates in the Metabolic Adaptations to Low Phosphate in Arabidopsis

Abstract: Phosphate is a major plant macronutrient and low phosphate availability severely limits global crop productivity. In Arabidopsis, a key regulator of the transcriptional response to low phosphate, phosphate starvation response 1 (PHR1), is modulated by a class of signaling molecules called inositol pyrophosphates (PP-InsPs). Two closely related diphosphoinositol pentakisphosphate enzymes (AtVIP1 and AtVIP2) are responsible for the synthesis and turnover of InsP8, the most implicated molecule. This study is focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 66 publications
0
28
0
Order By: Relevance
“…This increase in P i accumulation in severe DDP1 OX lines was also significantly higher than P i accumulation in ipk1 mutants (Figure 5a). This is notable as past studies demonstrate ipk1 mutants accumulate significantly higher P i compared to WT (Stevenson-Paulik et al ., 2005; Kuo et al ., 2014; Kuo et al ., 2018; Land et al ., 2021). Under our conditions, ipk1 mutants had higher P i from WT only after 4 weeks of growth whereas all other ipk1 timepoints showed no statistical difference in P i accumulation (Figure 5a).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This increase in P i accumulation in severe DDP1 OX lines was also significantly higher than P i accumulation in ipk1 mutants (Figure 5a). This is notable as past studies demonstrate ipk1 mutants accumulate significantly higher P i compared to WT (Stevenson-Paulik et al ., 2005; Kuo et al ., 2014; Kuo et al ., 2018; Land et al ., 2021). Under our conditions, ipk1 mutants had higher P i from WT only after 4 weeks of growth whereas all other ipk1 timepoints showed no statistical difference in P i accumulation (Figure 5a).…”
Section: Resultsmentioning
confidence: 99%
“…PP-InsP signaling in plants has become an increased area of interest due to emerging evidence connecting the role of PP-InsPs to P i sensing and other hormone signaling pathways (Laha et al ., 2015; Kuo et al ., 2018; Adepoju et al ., 2019; Laha et al ., 2019; Zhu et al ., 2019; Laha et al ., 2020; Land et al ., 2021). In this work, we sought to use a synthetic biology approach to manipulate PP- InsPs in transgenic plants to study the long-term consequences of decreased PP-InsPs, and to evaluate the preliminary translational potential of depleting PP-InsPs in planta .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, Arabidopsis Atipk1 and Atitpk1 mutants which are defective in the synthesis of IP 5 and IP 6 are also altered in Pi homeostasis (Kuo et al 2018), suggesting that speci c species of IP might play a speci c role in the regulation of plant Pi homeostasis and that it is not solely controlled by IP 8 . In support of this notion, a recent report of novel alleles of Atvih1 and Atvih2 double mutants showed that IP 8 levels are downregulated in these mutants, however, the expression of AtPHR1 targets remains responsive to Pi deprivation (Land et al 2021). Because IP 6 , IP 7 and IP 8 can bind the SPX domain (Wild et al 2016), further in planta studies on the speci c roles of IPs individual species are required.…”
Section: Regulation Mechanisms By Inositol Polyphosphate Sensingmentioning
confidence: 90%